Predictive Cancer Detection and Treatment Using Machine Learning and Artificial Intelligence (International Journal of Innovative Research in Engineering & Management, 2022)
erive meaningful insights through Big  Data. With emerging technology, Machine Learning can  now be used to predict almost any result according to any  functionality. Machine Learning studies underlying patterns  in the data and thus derives a suitable model. Medical  Sciences face new challenges every day for example,  illiteracy in patients about the actual diseases they are  facing, taking further steps in treatments, medications  needed to treat diseases and so on. This project will help  patients to detect cancer and guide patients to proceed with  the correct treatments through the mere input of symptoms  faced, medical histories if any, current medical reports like  blood, pathology, heart, ECG, etc. The model will thus be  able to represent itself just how a doctor can, to patients.
Keywords: Machine Learning; Artificial Intelligence; Diagnosis; Health Care Prediction